Analyse lineaire de coques minces elastiques par deux MEF non conformes - Palma, Francisco Jose; Vilariiio, Angeles (European Journal of Computational Mechanics, 1997)
In this paper, we apply the Morley’s and Sander’s nonconforming finite element methods to approximate the solution of general thin shell problems, following the Koiter’s linear model. We calculate the basis functions and we analyse the numerics results over some test problems.